BS EN 50065-2-3. Signalling on low-voltage electrical installations in the frequency range 3 kHz to 148, 5 kHz. Part 2-3. Immunity requirements for mains communicating equipment operating in the range of frequencies 3 kHz to 95 kHz and intended for use by electricity suppliers and distributors (23rd September 2020) - British Standards Institution,
No abstract available